Amide-functionalized graphene with 1, 4-diaminobutane as efficient metal-free and porous electrocatalyst for oxygen reduction. (January 2017) - Ahmed, Mohammad Shamsuddin; Kim, Young-Bae
Abstract: A porous graphene catalyst was prepared with 1, 4-diaminobutane (DAB) through amide functionalization and was used as a metal-free electrocatalyst for oxygen reduction reaction (ORR) in alkaline fuel cells. DAB was used as a junction among functionalized graphene layers to impart electrocatalytic activity for the ORR resultant from the interlayer charge transfer. The successful amidation and subsequent reduction in the process of catalyst preparation were confirmed using X-ray photoelectron spectroscopy. A hierarchical porous structure was also confirmed through the surface morphological analysis. The Brunauer–Emmett–Teller specific surface area and thermal stability increased by 2.6- and 1.5-fold, respectively, after successful amide functionalization. The as-prepared catalyst was proved an efficient metal-free electrocatalyst with better electrocatalytic activity, stability, and tolerance to the crossover effect than commercially available Pt/C for ORR by a direct four-electron involved pathway. These results indicate that the amide-functionalized graphene metal-free catalyst reported in this study is a promising alternative to traditional noble metal-based ORR catalysts. Graphical abstract: